A systematic examination of classical and multi-center bonding in heteroborane clusters - Melichar, Petr; Hnyk, Drahomír; Fanfrlík, Jindřich (Physical chemistry chemical physics, 2018)
This paper presents a systematic study of multicenter and classical bonding on a broad series of experimentally known heteroboranes covering closo, nido, arachno and hypho types of cages with incorporated tetrel, pnictogen or chalcogen heterovertices up to the third-row elements. The nature of bonding is studied using a novel quantum-chemical tool, the intrinsic atomic/bond orbital (IAO/IBO) approach, which provides a direct connection between quantum chemistry and chemical concepts. We also discuss how the computed IBO properties are related to molecular observables such as interatomic distances, molecular electrostatic potential surfaces and dipole moments.